(The production of articficial "salak" flavor using instrumental method approach). - Timur Antara, Ngakan; -, Hendarti; Sapto Hartanto, Eddy (Warta Industri Hasil Pertanian, 1993)
The study imitating "salak" (fruit of salacce edulis) has been done by instrumentation approach.Six components of "salak" flavor,which are probably the key-flavor of "salak" were identified.By compounding the identified components namely ethyl butyrate,isoamyl acetate,alyl caproate,amyl butyrate,linalool and geraniol with another chemical such as aldehyde C19,diphenyl oxide,peru balsam,lemon oil,lime oil,glyserine,ethanol 96%,propylene glycol and cananga oil originated from irian,the artificial "salak" flavor has been created successfully.From the sensory point of view all of panels detected the "salak" flavors of the product,and 6 out of 21 detected another flavor beside the "salak" flavor it self.